Auditoría de gestión y proceso administrativo en la Facultad de Ciencias Económicas y de Negocios en la Universidad Nacional de la Amazonía Peruana 2023 - Baluarte Navarro, Karla Fernanda (2025)
This research focuses on the relationship between the management audit and the administrative process in the Faculty of Economics and Business Sciences of the National University of the Peruvian Amazon in 2023. The general problem of what is the relationship between these two variables is formulated and specific objectives are set out that seek to determine how the controlled environment, control actions, communication and monitoring are related to the administrative process of the faculty. The methodology employed is of a basic type, with a correlational level and a transversal non-experimental design, which allows the interactions between the variables to be analysed at a specific moment in time. The results indicate that there is a significant relationship between performance auditing and the administrative process, suggesting that the implementation of appropriate auditing practices can improve the administrative efficiency and effectiveness of the faculty. The findings highlight the importance of strengthening internal control systems and communication in the administrative context, as well as the need for performance audits to ensure that institutional objectives are met. This study offers a model that can be replicated in other educational institutions to optimise their administrative processes and improve the quality of the educational service.